Early PARacetamol (EPAR) trial: a study protocol for a randomised controlled trial of early paracetamol to promote closure of the ductus arteriosus in preterm infants - Kei Lui; Srinivas Bolisetty; Tim Schindler; John Smyth; Joanna Michalowski (BMJ Open)
Introduction The optimal management of patent ductus arteriosus (PDA) remains contentious. The medications used to treat PDA are often non-steroidal anti-inflammatory drugs, which are associated with a number of unwanted adverse effects. Paracetamol is a medication with an excellent safety profile in infants and has been suggested as a safe alternative medication in situations where other medications have failed or are contraindicated. There are limited data on the use of early, intravenous paracetamol in preterm infants.Methods and analysis This trial aims to address whether early treatment with paracetamol will reduce the number of infants requiring intervention for PDA. This is a randomised, double-blind, placebo-controlled trial in preterm infants <29 weeks’ gestation. At 6 hours of life, infants with a ductus arteriosus >0.9 mm will be randomised to receive either (1) intravenous paracetamol at a dose of 15 mg/kg initially, followed by every 6 hours at a dose of 7.5 mg/kg for 5 days; or (2) intravenous 5% dextrose every 6 hours for 5 days. The primary outcome is the need for any intervention for management of PDA up to 5 days. Secondary outcomes include closure of the ductus arteriosus at 5 days, size of the ductus arteriosus, ductal reopening, systemic blood flow, mortality and significant morbidities. The target sample size of 100 infants yields >80% power, at the two-sided 5% level significance, to detect a 50% reduction in the need for intervention assuming that approximately 60% of infants in this study would otherwise have required intervention for PDA.Ethics and dissemination A report on the results of the planned analyses will be prepared. The results of the primary analysis of all end points will be presented at medical conferences and submitted for publication in peer-reviewed journals. Separate manuscripts pertaining to the second aim of the study may be written, and these will also be submitted for publication in peer-reviewed journals.Trial registration number ACTRN12616001517460.